MODEL PENGELOLAAN KEUANGAN DESA MELALUI PROSPEKTIF PENGAWASAN BERBASIS MASYARAKAT - Susanti Hasan; Nur Mohammad Kasim; Lusiana Margareth Tijow (Maleo Law Journal, 2021)
The purpose of this study is to Analyze the Implementation of Village Financial Management according to Law Number 6 of 2014; Knowing the obstacles in realizing transparency in village financial management in Bone Bolango Regency; Creating an ideal Oversight Model in realizing transparency in Village Financial Management in Bone Bolango Regency. This research uses empirical legal research. Empirical legal research or in other terms commonly called sociological legal research or also called field research. The approach used in this study is the statute approach; Case Approach; and Conceptual Approach. The results of this study indicate: First, that the implementation of village financial management as mandated by the Law on Villages and Permendagri 20 of 2018 concerning village financial management. In the planning stage, some of the villages studied were in accordance with the procedures in accordance with the regulations, but the target time was not in accordance with the regulations. In the implementation phase of the village under study, the procedure was partly in accordance with the regulations even though the demands on the village government to realize transparency were not optimal. In the administration stage and the reporting stage in the villages studied it can be said to be in accordance with the rules even though the substance of the administration is not yet perfect then some villages can be said to be on time and in accordance with the regulations. Second, the obstacles in realizing transparency in the management of village finances at the location of the village under study can be concluded is the limited understanding of the Village apparatus on Regulation, the availability of human resources (HR), Community Participation and as well as supervision factors. Third, that in order to create an ideal Oversight Model for village financial management, researchers recommend a Community Based Monitoring Model which further strengthens the involvement of rural communities in the implementation of village development, not only from the planning and implementation aspects, but also is an involvement in supervision .Keywords: Transparency; Village Finance; Community-based supervision.